2014
DOI: 10.1002/chin.201452196
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: New Triterpenoids from the Fruiting Bodies of Ganoderma lucidum and Their Bioactivities.

Abstract: Two new triterpenoids (I) and (II) are isolated from the ethyl acetate extract of Ganoderma lucidum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ethanolic and EtOAc extract compounds 12 β -acetoxy-3 β , 7 β -dihydroxy-11, 15, 23-trioxolanost-8-en-26-oic acid butyl ester ( 71 ) from fruiting bodies of G. lucidium showed significant inhibition against S. aureus and B. subtilis with MIC values of 68.5  µ M and 123.8  µ M, respectively (positive control ampicillin = 4.1  µ M and 19.3  µ M, resp.) (Liu et al 2014). …”
Section: Antibacterial Activities Of Compounds and Extracts Of Ganodementioning
confidence: 99%
“…Ethanolic and EtOAc extract compounds 12 β -acetoxy-3 β , 7 β -dihydroxy-11, 15, 23-trioxolanost-8-en-26-oic acid butyl ester ( 71 ) from fruiting bodies of G. lucidium showed significant inhibition against S. aureus and B. subtilis with MIC values of 68.5  µ M and 123.8  µ M, respectively (positive control ampicillin = 4.1  µ M and 19.3  µ M, resp.) (Liu et al 2014). …”
Section: Antibacterial Activities Of Compounds and Extracts Of Ganodementioning
confidence: 99%
“…Since then, over 150 triterpenes were isolated including Ganoderic acid D, Ganoderic acid T, Ganoderic acid DM, and Ganodermanontirol [26]. Scientists have elucidated the orchestration of triterpenoid biological process in many publications [27]. Although the number of new triterpenoid identification is still growing, much attention has been focused on the pharmacological effects of medicinal fractions.…”
Section: The Active Ingredients In Ganoderma Lucidummentioning
confidence: 99%
“…It is used as a healthy food and traditional medicine for treating insomnia, amnesia, fatigue and expectoration in Chinese folklore and has been included in the Pharmacopeia of the People's Republic of China (2015 Edition) (11). Previous phytochemical studies have elucidated that the major phytochemicals in G. lucidum are triterpenoids (12,13), though steroids, fatty acids, nucleotides, nucleobases, lactones and alkaloids have also been reported (14)(15)(16). Pharmacological investigations on G. lucidum have revealed that it possesses various bioactivities, including anti-inflammation (17), anti-diabetes (18), neuroprotecion (19), and anti-cancer (20) properties.…”
Section: Introductionmentioning
confidence: 99%